The Arithmetic of Generalization for General Products of Monoids - Wazzan, Suha A. (Communications in Mathematics and Applications, 2021)
For \(A\) and \(B\) arbitrary monoids. In a recent work, Cevik et al. (Hacettepe Journal of Mathematics and Statistics 50(1) (2021), 224 - 234) defined new consequence of the general product denoted by \(A^{\oplus B}_{δ}\bowtie _{ψ }B^{\oplus A}\) and gave a presentation for this generalization. In this paper, we explore the way in which the structure of the generalization of general product reflects the properties of its associated wreath products.
Keywords: Product; Wreath product; Green's relations; Generalized Green's relations; Congruence; Transitive